1980
DOI: 10.1037/0033-2909.87.2.392
|View full text |Cite
|
Sign up to set email alerts
|

Sex bias in counseling and psychotherapy.

Abstract: The notion that existing research proves the sex bias inherent in counseling and psychotherapy is pervasive. Almost every subsequent study has taken as a major premise the finding by Broverman, Broverman, Clarkson, Rosenkrantz, and Vogel that clinicians hold different standards of mental health for men and women. In the present research, both the published and unpublished studies of sex bias in either counseling or psychotherapy were closely analyzed and their results integrated using meta-analytic techniques.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
99
1
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(101 citation statements)
references
References 30 publications
(30 reference statements)
0
99
1
1
Order By: Relevance
“…Anecdotal and survey evidence lead us to believe that such bias continues to exist and it results in less effective therapy (Davidson & Abramovitz, 1980), but to prove it definitively has been more difficult (Heatherington, Mazzarella and Stetts, 1986;Steams et al, 1980). Evidence regarding the measured effects of therapists' attitudes, whether reportedly biased or gender-fair, has been mixed; it is replete with methodological problems as is the evidence for effectiveness of therapy generally (Garfield, 1986;Heatherington, Mazzarella and Stetts, 1986;Orlinsky & Howard, 1980;Smith, 1980;Whiteley, 1979). Some have argued that a therapist's values and expectations do not matter as long as she or he is aware and does not impose them (Smith, 1980;Whiteley, 1979).…”
Section: Contemporary Implications For Counseling Psychotherapy and mentioning
confidence: 99%
See 1 more Smart Citation
“…Anecdotal and survey evidence lead us to believe that such bias continues to exist and it results in less effective therapy (Davidson & Abramovitz, 1980), but to prove it definitively has been more difficult (Heatherington, Mazzarella and Stetts, 1986;Steams et al, 1980). Evidence regarding the measured effects of therapists' attitudes, whether reportedly biased or gender-fair, has been mixed; it is replete with methodological problems as is the evidence for effectiveness of therapy generally (Garfield, 1986;Heatherington, Mazzarella and Stetts, 1986;Orlinsky & Howard, 1980;Smith, 1980;Whiteley, 1979). Some have argued that a therapist's values and expectations do not matter as long as she or he is aware and does not impose them (Smith, 1980;Whiteley, 1979).…”
Section: Contemporary Implications For Counseling Psychotherapy and mentioning
confidence: 99%
“…Evidence regarding the measured effects of therapists' attitudes, whether reportedly biased or gender-fair, has been mixed; it is replete with methodological problems as is the evidence for effectiveness of therapy generally (Garfield, 1986;Heatherington, Mazzarella and Stetts, 1986;Orlinsky & Howard, 1980;Smith, 1980;Whiteley, 1979). Some have argued that a therapist's values and expectations do not matter as long as she or he is aware and does not impose them (Smith, 1980;Whiteley, 1979). It would seem equally probable based on other evidence, that choice of therapeutic goals and processes can be influenced by the therapist's expectations.…”
Section: Contemporary Implications For Counseling Psychotherapy and mentioning
confidence: 99%
“…Noonan and Wilgosh (1981) indicated that androgyny has not "generated sufficient empirical support to warrant its use as a model of therapy" (p. 36) and Pyke and Stark-Adamec (1981) suggested "that androgyny is the penultimate phase of sex-role evolution and that the ultimate stage is sex-role transcendence" (p. 45). Smith (1980) has written the most significant article to date on the relationship of counsellor attitudes and values to the counselling process. Based on a metaanalysis of a large number of studies examining sex bias in counselling and psychotherapy, Smith made a convincing argument that sex-role biases attributed to counsellors are an artifact of the use of ambiguous stimulus objects in simulated counselling settings where sex is the only salient cue about the hypothetical client to which the therapist can respond.…”
Section: Skills Attitudes and Values In Counselling Womenmentioning
confidence: 99%
“…Particularly Stricker (1977) and Smith (1980) questioned a research literature which appeared to support the existence of bias against women in counselling. If that bias exists, it has yet to be demonstrated empirically in counselling process studies.…”
Section: The Feminist Movement and Counselling Womenmentioning
confidence: 99%
See 1 more Smart Citation